Paraphrases on the Epistles to Timothy, Titus, and Philemon, the Epistles of Peter and Jude, the Epistle of James, the Epistle of John, the Epistle to the Hebrews - Erasmus, Desiderius, -1536 (Erasmus, Desiderius, -1536. Works. 1984., 1993)
Erasmus yearned to make the Bible an effective instrument in the reform of society, church, and everyday life. He therefore composed paraphrases in which the words of Holy Scripture provided the core of a text, vastly expanded to embrace the reforming ̀philosophy of Christ.' The Paraphrases were successful beyond all expectations, and were quickly translated into French, German, English, and other languages.This is the fourth volume of Paraphrases to be published in the New Testament Scholarship Series in the CWE. The volume includes the Paraphrases on the Pastoral Epistles and the Catholic, or General, Epistles, as well as the Paraphrase on Hebrews. These books, in the biblical text, address the central issues of the Christian life within the context of family, church, and community. The Paraphrases sharpen the accent of the biblical message, speaking in an idiom appropriate to the sixteenth century but also surprisingly relevant to our own age: they condemn, for example, every form of tyrannizing in the home and self-aggrandisement in the church; perhaps above all, the Paraphrases expose the social injustice (inevitable, Erasmus would have us believe) of those who have acquired great personal wealth.Erasmus also reformulates, and sometimes develops, some of the great theological themes already defined in earlier volumes of this series. Is sin congenital, or do we sin simply in ̀imitation' of Adam? How do the Hebrew Scriptures attest to the presence of divine grace in the world before the birth of Christ? What is faith if not a vision of eternal realities so sure that we can clearly recognize the things of this passing world as the shadows they are?These Paraphrases address the modern reader with the relevance of the moral issues they define and the perennial importance of the theological questions they raise. Erasmus clarified and interpreted biblical text with immense rhetorical skill.